2022
DOI: 10.1039/d1cp04107j
|View full text |Cite
|
Sign up to set email alerts
|

A combined experimental and computational study on the transition of the calcium isopropoxide radical as a candidate for direct laser cooling

Abstract: Vibronically resolved laser-induced fluorescence/dispersed fluorescence (LIF/DF) and cavity ring-down (CRD) spectra of the (A_1 ) ̃(_^2)A^'/ (A_2 ) ̃(_^2)A^''-X ̃(_^2)A^' electronic transition of the calcium isopropoxide [CaOCH(CH3)2] radical have been...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…Although the FCF for CaO−adamantane (0.908) is worse than a those of M−O−Rs with certain smaller ligands, such as phenyl (0.933 41 ), the transition is not destroyed by adding a larger ligand. In fact, it has a better FCF than smaller molecules, such as CaOC 2 H 5 (<0.90 52 ) and CaOCH(CH 3 ) 2 (0.720 53 ), despite an increase in the number of vibrational modes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Although the FCF for CaO−adamantane (0.908) is worse than a those of M−O−Rs with certain smaller ligands, such as phenyl (0.933 41 ), the transition is not destroyed by adding a larger ligand. In fact, it has a better FCF than smaller molecules, such as CaOC 2 H 5 (<0.90 52 ) and CaOCH(CH 3 ) 2 (0.720 53 ), despite an increase in the number of vibrational modes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In this case it was the interest in laser cooling of molecules, like the metal hydroxides and alkoxides, to milli-and micro-Kelvin temperatures, for fundamental physics experiments and possible applications as quantum information devices. This interest prompted spectroscopic studies of the Ã2 E − X2 A 1 electronic transition in calcium methoxide [28], the Ã1 2 A ′′ / Ã2 2 A ′ − X2 A ′ transition in calcium ethoxide [29] and the Ã1 2 A ′ / Ã2 2 A ′′ − X2 A ′ transition in calcium isopropoxide [30]. The quite large number of vibrational modes in these molecules made it necessary to improve the efficiency of the construction of the H matrix and minimize its storage requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Functionalizing large molecules with optical cycling centers (OCCs) is being explored as a means for extending the exquisite control available in quantum information science to the chemical domain. Success requires that these OCCs absorb and emit many photons without changing their vibrational states. To accomplish this task, molecular design rules are being developed, aided and validated by experiments, to guide the creation of the ideal quantum functional groups. For example, prior work has demonstrated that alkaline earth alkoxides provide a general and versatile chemical moiety for optical cycling applications, as the alkaline earth radical electron can be excited without perturbing the vibrational structure of the molecule. ,, Similarly, traditional physical organic principles, such as electron-withdrawing, have been shown to improve OCCs performance. , Further, experimental and theoretical extensions to more complex acenes, , diamondoids, and even surfaces suggest an exciting path forward for creating increasingly complex and functional quantum systems.…”
mentioning
confidence: 99%